ALTERNATIVE SHEAR WALL DESIGN ON POLINEMA AC BUILDING STRUCTURE - Ikbarur Rohman; Trias Rahardianto; Agustin Dita Lestari Lestari (Jurusan Teknik Sipil Politeknik Negeri Malang, 2025)
Shear walls in high-rise buildings enhance resistance against lateral loads. This study compares the performance of four differentshear wall configurations in an eight-stories building designed with a dual structural system using the Response Spectrummethod, including structural period, shear force, story drift, and cost. Four shear wall configurations are planned: (1) ExistingCondition with Core Wall shear walls on the right and left sides (SW0); (2) Frame Wall in an L shape around the lift and stairs(SW1); (3) Two L shapes around the lift and stairs and two I shapes on the facade (SW2); and (4) I shapes around the lift, stairs,and facade (SW3). Simulations were conducted using ETABS, considering dead loads, live loads, and earthquake loads. Costestimate for shear walls of each alternative. Based on Structural Performance analysis Shear wall alternatives 2 (SW2) performsbest compared to others models. Based on the Cost Comparison SW0 is the cheapest among other configurations, however,from the structural performance perspective, SW2 & SW3 perform much better than those in SW0.